ANALISIS KEMAMPUAN LITERASI MATEMATIS SISWA SMP KELAS VIII PADA MATERI STATISTIKA - ROHENDI ROHENDI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The purpose of this study was to determine and analyze students' mathematical literacy abilities. The results of the 2018 PISA Study show that mathematical literacy skills in numeracy of students in Indonesia are still in the low category by getting a score of 379 with an average score of 487. Class VIII students of SMPN 1 Saguling West Bandung participated in this study as the research population. This classroom action research is planned to consist of 2 (two) cycles. First, a primary test is conducted which aims to determine students' basic abilities and relate them to statistical material. In the first cycle, the percentage of students who answered the questions correctly was 64.8%. Based on the results of the first cycle test, it can be said that students' literacy skills are still relatively weak. However, in the results of the study the final score showed that the mathematical literacy ability of class VIII SMPN 1 Saguling students, 15 students had abilities in the High category, 6 students in the Medium category and 14 students in the Low category. Increasing the level of mathematical literacy skills needs to be done to catch up with the mathematical literacy skills of students in Indonesia. ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui dan menganalisis kemampuuan literasi matematika siswa. Hasil Study PISA 2018 menunjukan bahwa kemampuan literasi matematika dalam numerasi siswa di Indonesia masih dalam kategori rendah dengan mendapat skor 379 dengan skor rata-rata 487. Siswa kelas VIII SMPN 1 Saguling dengan jumlah 35 orang siswa sebagai populasi penelitian. Penelitian tindakan kelas ini direncanakan terdiri dari 2 (dua) siklus. Pertama, dilakukan tes primer yang bertujuan untuk mengetahui kemampuan dasar siswa dan menghubungkannya dengan materi statistika. Pada siklus pertama, persentase siswa yang menjawab pertanyaan dengan benar adalah 64,8%. Berdasarkan hasil tes siklus I dapat dikatakan bahwa kemampuan literasi siswa masih tergolong lemah. Namun, dalam hasil penelitian skor akhir menunjukan bahwa kemampuan literasi matematika siswa kelas VIII SMPN 1 Saguling, 15 siswa memiliki kemampuan dalam kategori Tinggi, 6 siswa dengan kategori Sedang dan 14 siswa dalam kategori Rendah. Peningkatan level kemampuan literasi matematika perlu dilakukan untuk mengejar ketertinggalan kemampuan literasi matematika peserta didik di Indonesia.